Performance Analysis of Government Regional Revenue and Expenditure Budget (APBD) Management - Ismiyana, Ulydhatul; Parinduri, Ramadha Yanti; Awaliah, Andi Urfia; Riduan, Akhmad; Afrizal, Afrizal (Jurnal Economic Resource, 2025)
The Regional Revenue and Expenditure Budget (APBD) is the primary instrument used by local governments to achieve development goals and enhance community welfare. Through the APBD, local governments plan and manage regional revenues and expenditures in a budget year. Therefore, the effectiveness and efficiency of APBD management are important indicators in assessing local government performance. This type of research uses a qualitative descriptive approach. The objective of this research is to examine the financial performance of the Indonesian government, specifically the Performance Analysis Report on the Management of the Regional Revenue and Expenditure Budget (APBD) of the Indonesian government. This research utilizes secondary data sourced from official government documents in Indonesia. The data analysis technique employed in this research utilizes the Balanced Scorecard method. The results of this study have found that by using the Balance Scorecard method, namely: (1) Based on the independence ratio, the City government has shown delegative results. (2) Based on the revenue effectiveness ratio, the City government has succeeded in achieving targets or objectives effectively. (3) The Customer Satisfaction Perspective uses the public satisfaction index (IKM) of government. (4) The Internal Process Perspective of Bureaucratic Reform uses the bureaucratic reform index (IRB) of the city in 2023 - 2025, which shows a significant increase. From 2023 to 2025, Indonesia is expected to see an increase in the percentage of SMEs. (4) The growth and learning perspective using the city employee quality index in 2023 – 2025 shows that the quality of employees who have participated in training and development is very high.